Secure Multiterminal Source Coding With Actions - Lu, Jian; Xu, Yinfei; Zhang, Ping; Wang, Qiao (Proceedings / IEEE International Symposium on Information Theory, 2019)
This paper studies the secure multiterminal source coding problem with actions. In particular, one main encoder observes an independent and identically distributed (i.i.d.) source X n and wishes to compress this source lossyly to the decoder. Another encoder observes the source Y n and wants to compress this source losslessly to the decoder. A passive eavesdropper having access to the side information Z n can observe the information bits sent by the main encoder. In this scenario, the decoder is allowed to choose actions affecting the correlated source Y n and the side information Z n . For this problem, we characterize the optimal rate-distortion-cost-leakage region for a discrete memoryless setting.